Elemental interdiffusion in W-Ta composites developed for fusion applications - Mateus, R. (2014)
Tungsten (W) was select for an extensive use in nuclear fusion devices due to its low neutron activation, high melting point and sputtering threshold as well as low hydrogen inventory. Nevertheless, W is brittle at low and moderate temperatures, which results in abnormal thermal stress, component fracture and extra erosion under reactor operation due to inherent thermal cycling events. An attractive way to solve these problems involves the addition of other refractory metals in the W matrix and tantalum (Ta) is a natural candidate. It has a high ductility, toughness and radiation resistance relative to those of W and transmutes to W by high-energy neutron irradiation. Recently, IST proposed the production of W-Ta composite by mechanical synthesis.